2021
DOI: 10.1093/ntr/ntab168
|View full text |Cite
|
Sign up to set email alerts
|

Instigators of COVID-19 in Immune Cells Are Increased in Tobacco Cigarette Smokers and Electronic Cigarette Vapers Compared With Nonsmokers

Abstract: Introduction The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the virus responsible for the COVID-19 pandemic, gains entry into the host cell when its Spike protein is cleaved by host proteases TMPRSS2 and furin, thereby markedly increasing viral affinity for its receptor, angiotensin-converting enzyme-2 (ACE2). In rodent and diseased human lungs, tobacco cigarette (TCIG) smoke increases ACE2, but the effect of electronic cigarette vaping (ECIG) is unknown. It is unknown whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
(27 reference statements)
2
9
1
Order By: Relevance
“…Propolis may be a healthy substance for strengthening immune systems (35); however, there is no evidence to support that use of these substances or vaping these substances can protect individuals from getting or treating COVID-19. Given that the effect of vaping such substances on COVID-19 is still unclear, (36)(37)(38)(39)(40) these videos are disseminating unconfirmed health information.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis may be a healthy substance for strengthening immune systems (35); however, there is no evidence to support that use of these substances or vaping these substances can protect individuals from getting or treating COVID-19. Given that the effect of vaping such substances on COVID-19 is still unclear, (36)(37)(38)(39)(40) these videos are disseminating unconfirmed health information.…”
Section: Discussionmentioning
confidence: 99%
“…Little work has been done in this area, but studies have shown that particulate matter (a known pathogenic component of cigarette smoke) increased ACE2 and TMPRSS2 expression in murine lung macrophages [ 66 ]. One study showed that ACE2 and TMPRSS2 was increased in CD45+ immune cells, which would include macrophages, of smokers and vapers [ 71 ]. Another study utilising a ferret SARS-CoV-2 infection model found that blood monocyte-derived macrophages were the most common infiltrated immune cells in the lungs, and the macrophages showed the presence of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…All participants had refrained from smoking 12 h before the study session. Healthy male and female volunteers with previously described characteristics [11] between the ages of 21 years and 45 years were eligible for enrollment if they were chronic (> 1 year), as follows: (1) active TCIG smokers (regardless of the number of pack-years) or (2) ECIG vapers (no dual users) or (3) non-smokers. Former TCIG smokers were eligible to be included in the nonsmoker group, if greater than 1 year had elapsed since quitting.…”
Section: Study Participantsmentioning
confidence: 99%
“…End-tidal CO, elevated > 10 ppm in smokers, was measured in EC vapers and non-smokers to confirm none was surreptitiously smoking TCIGs. Current smoking/vaping burden was estimated by plasma cotinine levels as previously described [11]. The experimental protocols were approved by the UCLA Institutional Review Board (IRB#18-001,147), and all participants provided written informed consent.…”
Section: Study Participantsmentioning
confidence: 99%